Small-sized milk processing plant considerations - B. Macias Rosario; L. McVay; Fadi M. Aramouni; Karen A. Schmidt (Kansas Agricultural Experiment Station Research Reports, 2003)
Milk is widely considered one of the world's most valuable foods. As a raw material, it is available in various forms, and is found in an ever-increasing variety of nutritional products. Milk is a complex biological fluid consisting of the following components: water (87.4%), sugar or lactose (4.8%), fat (3.7%), protein (3.4%), minerals (0.7%), as well as minute amounts of vitamins. This document presents the standards, process needs, and labeling requirements of pasteurized fluid milk for the state of Kansas.; Dairy Day, 2003, Kansas State University, Manhattan, KS, 2003;
Keywords: Dairy Day; 2003; Kansas Agricultural Experiment Station contribution; no. 04-129-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 919; Dairy; Raw milk standards; Processed milk standards; Processed milk equipment